2019
DOI: 10.1111/hepr.13300
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin‐altered gut microbiota components associated with liver/neuropsychological functions in patients with hepatic encephalopathy: An exploratory data analysis of phase II/III clinical trials

Abstract: AimsRifaximin (RFX), a non‐systemic antibiotic, improves liver/neuropsychological functions in patients with hepatic encephalopathy (HE). We aimed to investigate the clinical profiles associated with gut bacterial loads using exploratory data analysis and the effects of RFX on the gut microbiota of patients with HE.MethodsWe analyzed the data from 17 patients with HE who underwent fecal microbiota examination in phase II/III trials in Japan. Profiles associated with genera Streptococcus, Veillonella, and Lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Sung et al [ 43 ] confirmed that fecal microbiota can predict the clinical prognosis of patients with liver cirrhosis and HE, such as Lactobacillus , Bacteroides , Clostridium_incertae_sedisof , and Clostridium XI , which were associated with patients' mortality. Furthermore, Kawaguchi et al [ 172 ] showed that rifaximin improved both liver and neuropsychological function in liver cirrhosis patients with HE by adjusting the gut microbial structure.…”
Section: Other System-related Neurological Diseasesmentioning
confidence: 99%
“…Sung et al [ 43 ] confirmed that fecal microbiota can predict the clinical prognosis of patients with liver cirrhosis and HE, such as Lactobacillus , Bacteroides , Clostridium_incertae_sedisof , and Clostridium XI , which were associated with patients' mortality. Furthermore, Kawaguchi et al [ 172 ] showed that rifaximin improved both liver and neuropsychological function in liver cirrhosis patients with HE by adjusting the gut microbial structure.…”
Section: Other System-related Neurological Diseasesmentioning
confidence: 99%
“…5 Also, the non-absorbable antibiotic rifaximin, which inhibits the activity of urease-producing bacteria, and alters the gut microbiota. 5,6 Nevertheless, the therapeutic response rate to these treatments is not uniform and other therapies are limited. Moreover HE patients often show poor compliance and adherence to these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Rifaximin has also been reported to shorten the duration of treatment for HE in inpatient settings, resulting in higher cost‐effectiveness of treatment 22 24 Studies on the efficacy of rifaximin and intestinal bacterial flora showed that although total bacterial volume did not change with rifaximin therapy, the volume of Veillonella and Streptococcus species was relatively lower, which suggests that rifaximin might alter intestinal bacterial flora and restore intestinal permeability, thereby reducing neuropsychiatric symptoms 25 26 Given that the therapeutic and prognosis‐improving effects of rifaximin in patients with hepatic cirrhosis have been verified extensively worldwide, 3 , 4 , 9 , 27 and prospective randomized comparative studies cannot be conducted easily, the present results suggest that rifaximin is efficacious for OHE in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%